FORENSIC APPRAISAL OF CARRION INSECTS FOUND ON DOMESTIC FOWLS POISONED WITH SNIPER INSECTICIDE - Tyokumbur, Emmanuel; Ogunlade, Fredrick (FUDMA JOURNAL OF SCIENCES, 2023)
A study was carried out on the forensic entomotoxicological appraisal of carrion insects of domestic fowl poisoned with dichlorvos (sniper insecticide) between October and December 2019 on the campus of University of Ibadan. Sniper as a common suicide agent in Nigeria needs to be studied using animal models. Two domestic fowls were euthanized with 3 ml and 5 ml of dichlorvos respectively. Adult carrion insects were collected from the carrions using a sweep net and stored in silica gel. The larvae were collected and preserved in 70% ethanol while pupae were collected using forceps. Ambient and carcass temperature were measured using infrared thermometer while relative humidity was recorded from digital hygrometer. Calliphoridae and Muscidae were the initial colonizers of the decomposing carcass and were dominant followed by Sarcophagidae. The defeathered domestic fowl had more abundance and species composition of carrion insects than the feathered. The length and weight of the larvae as indices of growth were comparatively higher in the defeathered domestic fowl. The highest mean carcass temperature  was 30.50 C while the lowest was 22.60C. The highest carcass temperature was recorded on the seventh day during the active decomposition stage. The highest mean relative humidity value was 85% while the least recorded was 60%. Overall, fast decomposition rate was recorded due to high ambient and carcass temperatures. It can be deduced that carrion insects are essential in providing the essential ecosystem service of decomposition and can be used in solving suicide puzzles through the extrapolation of post mortem intervals.
Keywords: Entomotoxicology; Dichlorvos; Domestic fowl; Carrion insects; Decomposition